Analisis Strategi Pengembangan Usaha Pempek Kak Yan 147 Di Kota Jambi - Geofanny, Riky; Dahmiri, Dahmiri; Sari, Novita (Jurnal Dinamika Manajemen, 2024)
This research aims to provide an overview of the development strategy for the Pempek Kak Yan 147 business in Jambi City. This research uses qualitative methods by conducting interviews. This research draws on sources from business owners, employees and consumers. This research also carries out a SWOT analysis in determining business development strategies. The results of this research are that this business has strengths in affordable prices and delicious taste, but this business also has weaknesses in product marketing and the lack of variety in pempek. So the researchers designed a strategy for developing the Pempek Kak Yan 147 business, namely, 1) Offering more affordable prices with good quality taste and providing good service, 2) Strategic business location provides opportunities for consumers to shop easily, 3) Establishing relationships good with consumers and expand sales distribution reach.